Will the Web break? - Zittrain, Jonathan (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2013)
What is the Web? What makes it work? And is it dying? This paper is drawn from a talk delivered by Prof. Zittrain to the Royal Society Discussion Meeting 'Web science: a new frontier' in September 2010. It covers key questions about the way the Web works, and how an understanding of its past can help those theorizing about the future. The original Web allowed users to display and send information from their individual computers, and organized the resources of the Internet with uniform resource locators. In the 20 years since then, the Web has evolved. These new challenges require a return to the spirit of the early Web, exploiting the power of the Web's users and its distributed nature to overcome the commercial and geopolitical forces at play. The future of the Web rests in projects that preserve its spirit, and in the Web science that helps make them possible.